Acute shear stress direction dictates adherent cell remodeling and verifies shear profile of spinning disk assays. (21st January 2015) - Fuhrmann, Alexander; Engler, Adam J
Abstract: Several methods have been developed to quantify population level changes in cell attachment strength given its large heterogeneity. One such method is the rotating disk chamber or 'spinning disk' in which a range of shear forces are applied to attached cells to quantify detachment force, i.e. attachment strength, which can be heterogeneous within cell populations. However, computing the exact force vectors that act upon cells is complicated by complex flow fields and variable cell morphologies. Recent observations suggest that cells may remodel their morphology and align during acute shear exposure, but contrary to intuition, shear is not orthogonal to the radial direction. Here we theoretically derive the magnitude and direction of applied shear and demonstrate that cells, under certain physiological conditions, align in this direction within minutes. Shear force magnitude is also experimentally verified which validates that for spread cells shear forces and not torque or drag dominate in this assay, and demonstrates that the applied force per cell area is largely independent of initial morphology. These findings suggest that direct quantified comparison of the effects of shear on a wide array of cell types and conditions can be made with confidence using this assay without the need for computational or numerical modeling.